Programa De Atención E Intervención Psicosocial Orientado Desde El Metapropósito De Rehabilitación Psicosocial Con Mujeres Víctimas De Violencia Intrafamiliar Usuarias De La Comisaría De Familia Del Municipio De Cajicá (2021)
According to the situation that is currently occurring in the world called the Covid-19 pandemic defined by the WHO as "A public health emergency of international concern"; the figures compared to the VI, have increased by 175%, and according to data obtained by the report of the Colombian Women's Observatory (OCM), the most affected cities have been Bogotá (37%), Antioquia (12%), Valle del Cauca (9%), Cundinamarca (7%) and Atlántico (5%) calling it, as well as the silent pandemic (OCM), 2020, p.3)